1983
DOI: 10.1113/expphysiol.1983.sp002758
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐evoked Opening of Potassium Channels in Hamster Eggs

Abstract: SUMMARYMeasurements of membrane potential and resistance have been made in zona-free hamster eggs. The resting potential lay in the range -9 to -100 mV and the input resistance fell in the range 14 to 440 MQ; high resting potentials were associated with large input resistances. Calcium injected ionophoretically into an egg from an intracellular micro-electrode caused a reduction of the membrane resistance. The estimated reversal potential for the calcium-evoked response was about -80 mV and its amplitude depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…This suggests that the relative sodium permeability of the mouse egg is not Previous electrophysiological studies (Powers & Tupper, 1974;Okamoto et al 1977;Miyazaki & Igusa, 1982;Georgiou et al 1983) have reported a slight influence of potassium ions on the resting potential ofmouse and hamster eggs. However, these experiments were carried out on eggs depolarized by impalement-leak artifacts and therefore it was necessary to re-examine the effect of potassium on potential and resistance.…”
Section: Effect Of Ionic Substitutionmentioning
confidence: 98%
See 1 more Smart Citation
“…This suggests that the relative sodium permeability of the mouse egg is not Previous electrophysiological studies (Powers & Tupper, 1974;Okamoto et al 1977;Miyazaki & Igusa, 1982;Georgiou et al 1983) have reported a slight influence of potassium ions on the resting potential ofmouse and hamster eggs. However, these experiments were carried out on eggs depolarized by impalement-leak artifacts and therefore it was necessary to re-examine the effect of potassium on potential and resistance.…”
Section: Effect Of Ionic Substitutionmentioning
confidence: 98%
“…Moreover, when a second micro-electrode is inserted into a hamster or mouse egg after the high potential and resistance state is attained there is always a transient fall both in the potential and the resistance of the egg (Fig. 4, Georgiou et al 1983; Fig. 1, present study) as would be expected for a transient leak pathway at the micro-electrode tip.…”
Section: Does Micro-electrode Insertion Mimic Sperm Entry?mentioning
confidence: 99%
“…Although the presence of Ca2+-activated K+ channels has been demonstrated in mammalian eggs (e.g. Miyazaki & Igusa, 1983;Georgiou et al 1983) Cl-channels also activated by calcium exist in Xenopus oocytes (Barish, 1982;Miledi & Parker, 1984) and so it was necessary to test for the latter type in hamster eggs. Methane sulphonate is a useful replacement anion for Cl-as it is impermeant and does not alter intracellular pH (Sharp & Thomas, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Voltage-clamp studies (Okamoto, Takahashi & Yamashita, 1977) and intracellular recordings (Miyazaki & Igusa, 1982;Georgiou et al 1983) The mean maximum rate of rise at pH. = 7-5 was 1P7+0-2 V/s (n = 12).…”
Section: -3+6-6mentioning
confidence: 99%
See 1 more Smart Citation